Acúmulo de biomassa e compostos lignocelulósicos em híbridos de sorgo sensíveis ao fotoperíodo - Castro, Fernanda Maria Rodrigues (2018)
Biomass sorghum has particularities that allow its use as raw material for bioenergy production, but its industrial destination is the result of agronomic and technological factors association, related to the productivity and the lignocellulosic compounds concentration. The objective in this study was to analyze the growth, accumulation of biomass and lignocellulosic compounds in biomass sorghum hybrids sensitive to the photoperiod, as well to evaluate the interactions with the environment in different phenological phases, using growth rates absolute and relative of the culture. The experiments were conducted in Lavras and Sete Lagoas in the Minas Gerais state, in the crop seasons 2014/2015 and 2015/2016. A complete randomized block design with a factorial scheme 4 x 6, being four hybrids (BRS716, CMSXS7027, CMSXS7045, CMSXS7046) and six evaluation periods (30, 60, 90, 120, 150, 180 days after planting), with three replications. The agronomic assessed traits were: plant height (PH), green mass yield (GMY), dry mass yield (DMY); and the technological traits: cellulose (CEL), hemicellulose (HEM) and lignin (LIG). The average performance of the hybrids throughout the evaluation periods in the harvests and tested sites were adjusted by means of a logistic regression model and, posteriorly, absolute crop growth (AGR) and relative crop growth (RGR) rates were estimated. The traits that did not fit to the logistic model were adjusted to the polynomial regression model. The hybrids showed different behavior for the PH, CEL and LIG traits. From the absolute and relative growth rates, there were considerable increases in the initial phases of the vegetative cycle for these traits, standing out the BRS716 hybrid because it presents growth rate in relation to PH and accumulation of CEL higher than the others. The CMSXS7045 hybrid showed greater variation over time for the LIG content. Biomass sorghum hybrids, sensitive to the photoperiod, show a similar behavior during the evaluation periods for the PH, CEL and LIG traits. Through absolute and relative growth rates, considerable increase are observed in the early stages of the vegetative cycle (30 to 90 DAP) for the PH, CEL and LIG traits. It is verified the influence of the environments on the genotypes behavior during the evaluation periods for the PH, GMY, DMY and LIG traits. It is observed a greater increase in PH, GMY and DMY up to 90 days after planting, highlighting an accelerated growth rate and greater biomass accumulation for the environment of Sete Lagoas in both crop seasons.